Application of The Curriculum of Religious and General Fusion (Case Study in MA Unggulan K.H. Abd. Wahab Hasbulloh Jombang) - Chusnul Chotimah; Imam Taufiq (SCHOOLAR: Social and Literature Study in Education, 2021)
Quality education is the hope of every parent towards their child. This is done by choosing a good educational institution for the progress of the child and able to equip the child with character. Among the ways to determine a good school can be seen through the curriculum applied in the school. The purpose of this research is to know the application of religious and general curriculum at the research site and its value of excellence. The research was conducted using qualitative method with phenomenological perspective. Because it is covered in the Kementerian RI then this madrasah uses the curriculum 13 in accordance with the KMA 183. General and religious material content is applied with proportionally according to the program of interest in Religious Sciences, Social Sciences, and Mathematics of Natural Sciences. As a excellence value, students from all programs who are proficient in English and Arabic.